A high energy density asymmetric all-solid-state supercapacitor based on cobalt carbonate hydroxide nanowire covered N-doped graphene and porous graphene electrodes1. Issue 36 (28th September 2015) - Xie, Hao; Tang, Shaochun; Zhu, Jian; Vongehr, Sascha; Meng, Xiangkang
<x xml:space="preserve">Abstract</x> To achieve high energy densities, an asymmetric all-solid-state supercapacitor is developed with cobalt carbonate hydroxide (CCH) nanowire covered N-doped graphene (NG) as positive and porous NG as negative electrodes.